Aerobic fitness in late adolescence and the risk of cancer and cancer-associated mortality in adulthood: A prospective nationwide study of 1.2 million Swedish men. (April 2019) - Högström, G.; Ohlsson, H.; Crump, C.; Sundquist, J.; Sundquist, K.
Highlights: Higher aerobic fitness is associated with a reduced risk of cancer and cancer-associated mortality. The association is more pronounced for the later years of follow-up. The association is more pronounced for cancer-associated death compared to cancer. Accounting for familial factors slightly increased the protective effect of aerobic fitness. Abstract: Background: The incidence of cancer has steadily risen. It is important to identify modifiable predictors in early life that may decrease cancer risks and mortality. The present study aims to investigate the relationship between aerobic fitness in adolescence and the subsequent risk of cancer and cancer-associated mortality. Methods: The study included 1 185 439 Swedish men born between 1950 and 1980 that participated in the military conscription (mean age = 18 years). The results from the aerobic fitness test (Wmax ) was linked to the risk of cancer and cancer-associated mortality during a 40-years' follow-up using Cox proportional hazards models. A co-sibling design was employed to take familial factors into account. Results: During a mean follow-up of 27 years 15 093 cases of cancer and 4900 cancer-associated mortalities were registered. Higher Wmax (per additional 1 SD) was associated with a decreased risk of cancer at 40 years of follow-up (HR 0.93; 95% CI 0.91–0.96 for cancer and HR 0.82 95% CI 0.76–0.87 for cancer-associated mortality) but not at 5 years of follow-up (HR 1.03; 95% CI 0.99–1.07; and HR 1.04; 95% CI 0.97–1.12). In the co-sibling model the protective effects of high Wmax were increased at 40 years of follow-up for cancer (HR 0.91; 95% CI 0.85–0.98) and cancer-associated mortality (HR 0.78; 95% CI 0.68–0.89). Conclusions: These findings identify in late adolescence a potentially modifiable predictor of cancer, with higher aerobic fitness associated with a decreased risk of cancer incidence and mortality later in life.